(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study aimed to identify the role of training strategies in promoting the implementation of Total Quality Management (TQM) in Jordanian business organizations, as well as to determine the attitudes of employees in Jordanian telecommunications companies towards training strategies and TQM. The study employed a descriptive-analytical approach and used a questionnaire as the data collection tool. (450) questionnaires were distributed to the study sample, and (400) were returned. The data were analyzed using the Statistical Package for the Social Sciences (SPSS, Version 25) and descriptive statistics, including frequencies, percentages, Cronbach’s alpha coefficient, and simple regression. The study reached a number of conclusions, most notably: Employees in Jordanian telecommunications companies held highly positive attitudes towards all variables and dimensions of training strategies, with an overall mean of 3.61 and a standard deviation of 0.537. Regarding the availability of training strategy dimensions, E-training ranked first, followed by continuous training. The study sample also held highly positive attitudes towards all variables and dimensions of Total Quality Management (TQM), with a mean of 3.93 and a standard deviation of 0.206. Furthermore, the study revealed a role for training strategies in promoting the application of TQM principles in Jordanian telecommunications companies, along with a positive correlation between them (R = 0.471). E-training and continuous training also played a role in promoting TQM implementation in Jordanian telecommunications companies, demonstrating a positive correlation between them. The study offered several recommendations, the most important of which are: developing training strategies within the training programs of Jordanian telecommunications companies by activating e-training and focusing on the continuity of training, and working to establish a culture of quality dissemination within these companies.